EARLY PROTEROZOIC SYN-AND POSTCOLLISION GRANITES IN THE NORTHERN PART OF THE BAIKAL FOLD AREA - Larin A.M.; Sal'nikova E.B.; Yakovleva S.Z.; Kovach V.P.; Kotov A.B.; Makar'ev L.B. (My University, 2006)
Early Proterozoic granitoids are of a limited occurrence in the Baikal fold area being confined here exclusively to an arcuate belt delineating the outer contour of Baikalides, where rocks of the Early Precambrian basement are exposed. Geochronological and geochemical study of the Kevakta granite massif and Nichatka complex showed that their origin was related with different stages of geological evolution of the Baikal fold area that progressed in diverse geodynamic environments. The Nichatka complex of syncollision granites was emplaced 1908 ± 5 Ma ago, when the Aldan-Olekma microplate collided with the Nechera terrane. Granites of the Kevakta massif (1846 ± 8 Ma) belong to the South Siberian postcollision magmatic belt that developed since ~1.9 Ga during successive accretion of microplates, continental blocks and island arcs to the Siberian craton. In age and other characteristics, these granites sharply differ from granitoids of the Chuya complex they have been formerly attributed to. Accordingly, it is suggested to divide the former association of granitoids into the Chuya complex proper of diorite-granodiorite association ~2.02 Ga old (Neymark et al., 1998) with geochemical characteristics of island-arc granitoids and the Chuya-Kodar complex of postcollision S-type granitoids 1.85 Ga old. The Early Proterozoic evolution of the Baikal fold area and junction zone with Aldan shield lasted about 170 m.y. that is comparable with development periods of analogous structures in other regions of the world. © MAIK "Nauka/Interperiodica" 2006.
Keywords: BAIKAL FOLD AREA; EARLY PROTEROZOIC; GEOCHRONOLOGY; SOUTH SIBERIAN MAGMATIC BELT; SYN-AND POSTCOLLISION GRANITES; Палеозой::Кембрийская; Докембрий::Протерозой; Precambrian::Proterozoic; Paleozoic::Cambrian